Instructors' Conceptions of Minoritized College Students' Prior Knowledge and Their Related Teaching Practices. (29th July 2021) - Castillo-Montoya, Milagros; Ives, Jillian
ABSTRACT: Drawing on students' prior knowledge can enhance learning, but we know little about how instructors learn to teach with this knowledge in mind. Through a two-year embedded case study, we sought to examine how 10 college instructors' teaching conceptions and practices relevant to minoritized students' prior knowledge shifted over the course of two years. We found instructors' conceptions advanced further than their practices and the nature and extent of this shift differed by various factors including academic discipline; instructor social identity, particularly gender; teaching improvement goals; and instructor perceived or real teaching agency. Our findings have implications for understanding faculty as learners of teaching, as well as for academic administrators who want to support faculty as teachers.